2015
DOI: 10.4236/ojgas.2015.55009
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Irritable Bowel Syndrome among Medical and Non-Medical Suez Canal University Students

Abstract: Background: Irritable bowel syndrome (IBS) is one of the most frequently diagnosed gastrointestinal (GI) disorders in primary care and gastroenterology practices, despite the fact that many suffer symptoms without knowing their diagnosis or seek for medical consult, so this study aims to explore the prevalence of irritable bowel syndrome (IBS) among Suez Canal university students. Methods: A cross section with multistage cluster probability sample. Using Rome criteria III IBS module, the questionnaire was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
4
5
1
Order By: Relevance
“…In addition, the finding of the current study is consistent with the findings of Ahmed et al [10] who conducted a study in an urban area in Suez governorate and found that the prevalence of IBS among the studied population was 34.2%. On the other hand, the prevalence of IBS in the current study is higher than the findings of Darweesh et al [11] who conducted a study among students in Suez Canal University, Egypt and revealed that only 22.9% of the studied students were diseased and the findings of a study conducted in Karachi, Pakistan by Naeem et al [16] where the prevalence of IBS was found to be 28.3%. Results revealed that 39.2% of the diseased students had a mixed IBS type and 32.4% had constipation predominant IBS which is inconsistent with the findings of a study conducted among Japanese university students by Shiotani A et al [17] who revealed that the constipation predominant type was more prevalent (47.8%).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In addition, the finding of the current study is consistent with the findings of Ahmed et al [10] who conducted a study in an urban area in Suez governorate and found that the prevalence of IBS among the studied population was 34.2%. On the other hand, the prevalence of IBS in the current study is higher than the findings of Darweesh et al [11] who conducted a study among students in Suez Canal University, Egypt and revealed that only 22.9% of the studied students were diseased and the findings of a study conducted in Karachi, Pakistan by Naeem et al [16] where the prevalence of IBS was found to be 28.3%. Results revealed that 39.2% of the diseased students had a mixed IBS type and 32.4% had constipation predominant IBS which is inconsistent with the findings of a study conducted among Japanese university students by Shiotani A et al [17] who revealed that the constipation predominant type was more prevalent (47.8%).…”
Section: Discussioncontrasting
confidence: 56%
“…Females in this study represent 64.1% of the sample, 30.3% of them are diseased, while males represent 35.9% about 9.8% of them are diseased. IBS constipation predominant type is 28.2%, diarrhea predominant type is 15.4%, mixed type is 46.2%, and the un-subtyped cases represent 10.3% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, participants with enough and exceeding family income, in the current study, had a lower prevalence of IBS than others, which agree with numerous other studies [7,16,18]. This finding may have attributed to the "hygiene hypothesis" and its role in IBS [7].…”
Section: Discussionsupporting
confidence: 82%
“…The present study revealed that IBS-M and IBS-C were the commonest sub-types. This finding coincides with other studies from Pakistan [10] Saudi Arabia [16] and Egypt [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation